THE IMPLEMENTATION OF STRATEGIC MANAGEMENT TO IMPROVE FAMILY BUSINESS PERFORMANCE - Rochimat, Dedy; Irawan, Agustinus Purna; Suhartanto, Eko; Lim, Andriew (Graduate Program of Universitas Tarumanagara, 2023)
Family business is an important component in driving the national economy. Good and professional family business management has a positive impact on the company's performance which ultimately improves the welfare of the wider community. Family business requires professional involvement in its implementation. This is because not all fields can be done by family members alone, so appropriate professional assistance is required. This article discusses how to implement strategic management in managing a family business by involving professionals. The method of discussion in this paper is a descriptive analysis method accompanied by a case study of a family company that has become a successful company. Based on the results of the analysis, it can be concluded that the success of the family business is higher with the involvement professional assistance. The company's basic values ​​must be the basis for the management and needs to be implemented in various company policies in a professional manner. The results of the discussion in this article will be used as a reference in further research.